Makna Asosiatif dalam Lirik Lagu Asmalibrasi Grup Band Soegi Bornean - Kasmawati, Kasmawati (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research is a qualitative descriptive study. The aim of this study is to provide an overview of the forms and associative meanings in the lyrics of Asmalibrasi by the band Soegi Bornean. The data collection technique used in this study is literature study. The data analysis applies the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing or verification. The results of this study indicate that there are 14 instances of associative meaning. Keywords: Semantics, Associative Meaning, Song Lyrics, Soegi BorneanAminuddin. 1988. Semantik: Pengantar Studi Tentang Makna. Bandung: Sinar Baru Offset